In muliere virum faciat opus est - Božič, Anja (Bogoslovni vestnik, 2025)
The literary output of one of the earliest female humanist authors, Isot -ta Nogarola, has for the most part been examined through the lens of gender. According to prevailing interpretations, Nogarola is thought to have gained access to the predominantly male circles of the humanist rei publicae litterari-ae by deliberately suppressing her femininity, a strategy supposedly linked above all to either the absence of emotion or the expression of inferiority. In contrast, the present contribution shows that Nogarola incorporates feelings of submissiveness, humility, or alleged female weakness into established rhetorical strategies such as captatio benevolentiae. In similar manner, she enriches her works with self-ironic allusions to feminine loquacity while simultaneousl celebrating her gender through catalogues of illustrious women. She therefore does not suppress her sex; rather, she consciously foregrounds it and explicitly positions herself in her works as a female author.
Keywords: čustva; emotions; female authorship; humanism; humanizem; retorične strategije; rhetorics; women; žensko avtorstvo